Identification and structural characterization of pseudogenes in Fusarium graminearum - Domenico Rau; Chiara Maria Posadinu; Maria Leonarda Murgia; Davide Fois; Andrea Porceddu (Scientific Reports)
Abstract Pseudogenes can provide valuable insight into the evolutionary history of genomes which may be difficult to determine based on the examination of functional loci alone. This study presents the results of a comprehensive, two-stage genome-wide investigation into the identification and characterization of pseudogenes in Fusarium graminearum, the main causal agent of wheat head blight. By analyzing sequence homology between non-coding regions of the genome and predicted protein sequences, regions with homology to putative paralogous functional sequences were identified. These regions were characterized in terms of their matching sequence structure and position. Most of the pseudogenes identified were mapped within the fast-evolving genomic compartment and were derived from transposition events. The number of processed and putatively retroposed pseudogenes was found to be comparable. The low number of identified pseudogenes is consistent with the low number of gene duplicates in F. graminearum. No compelling evidence was found to suggest that pseudogene formation can be explained by evolutionary accidents during gene family expansion, nor that it is caused by RIP-associated mutagenic events. Notably, approximately one-third (144 of 436) of the pseudogenes were found to overlap with the untranslated or intron sequences of functional loci, suggesting that they could potentially be transcribed. Using comparative Fusarium genomics, we identified genomic regions with homology to genes lacking functional orthologues in F. graminearum. These were investigated as putative unitary pseudogenes, some of which had lost their original functions completely after the radiation of F. graminearum. Interestingly, the orthologous loci matching parents of the 18 loss-of-function pseudogenes showed homology to domains previously identified in proteins involved in pathogenesis.